AB0711 Optimizing Scleroderma Centers of Excellence: Perspectives From Patients and Systemic Sclerosis (SSC) Experts. (9th June 2015) - Jaeger, V.; Aubin, A.; Baldwin, N.; Fligelstone, K.; Sims, R.; Welling, J.; Burrill, R.; Connolly, K.; Gordon, J.K.; Frech, T.; Ngcozana, T.; Kowalczyk, M.; et al.
Abstract : Background: SSc is a complex, diffuse, devastating health condition of vascular injury, inflammation and fibrosis resulting in multiple organ involvement with high impact on survival and quality of life. Demonstrated research activity tends to define SSc Centers of Excellence (SCoE) certification. However, SSc complications require coordinated high-level multi-specialty expert care. The Scleroderma Foundation, Scleroderma Australia and Scleroderma Society UK engaged SSc patients and SSc health providers (HPs) in a multi-tiered process to assess priorities in recognition of SCoEs. Methods: A mixed methods design ensured comprehensive item collection in addressing "important qualities and services in a certified SSc Center of Excellence". A core of 35 patients & SSc HPs from 8 countries initiated the study through an iterative process using nominal group technique with rounds of item revision until saturation and satisfaction of proposed survey content was achieved and subsequently field-tested with a 5 point scale (critical to low importance). Participation was screened and "gate-controlled" with online survey access through a unique one-time link. Telephone interview was offered. Responses from SSc patients and HPs were compared by Pearson's χ 2 or Fisher's exact tests as appropriate. Results: Initial phases yielded a 54 item survey and field-tested in 15 SSc patients & HPs. 400 patients and SSc HPs received surveys of which 299 from 19 countries (75% response rate) were completers. Expert care superseded research as a priority of "critical importance" by HPs & patients respectively at 69% & 48% (p=0.02) and by 94% & 89% (p=0.8) when "critical to very important" were collapsed. 3 questions provided internal cross-validation of this query. "SCoEs should engage in research" received 57% of patients and 48% of HPs (p=0.37) as being critical. Further, education, rehabilitative services and support networks were consistently highly rated items with topics stratified by ratings (tables 1 & 2 ). Discrepant areas of importance between patients and HPs are highlighted in tables. Conclusions: Participation was robust in all project stages emphasizing the perceived global importance of this effort. Though research is of clear importance, quality expert care incorporating rehabilitative and educational provisions is a SCoE operational priority. These findings signal the need to redefine SCoE certification standards and provide a roadmap to SCoE development. Acknowledgements: Dedicated to the memory of Anne Mawdsley. Disclosure of Interest: V. Jaeger: None declared, A. Aubin: None declared, N. Baldwin: None declared, K. Fligelstone: None declared, R. Sims: None declared, J. Welling: None declared, R. Burrill: None declared, K. Connolly: None declared, J. Gordon: None declared, T. Frech: None declared, T. Ngcozana: None declared, M. Kowalczyk: None declared, M. Lammi: None declared, J. Lasky: None declared, U. Walker: None declared, L. A. Saketkoo Grant/research support from: ACR/EULAR Exchange Awardee